Relationship between levels of thyroid stimulating hormone, age, and gender, with symptoms of depression among patients with thyroid disorders as measured by the Depression Anxiety Stress Scale 21 (DASS-21) - Saidi, Sanisah; Jaafar, Siti Nur Illiani; Daud, Azlina; Musa, Ramli; Nik Ahmad, Nik Nur Fatnoon (Elsevier, 2018)
Objective: The aim of this study was to investigate the correlation between levels of depression symptoms and age, thyroid-stimulating hormone levels, and stressful life events of the participants. Method: Patients above 18 years old, with any thyroid disorders, and without psychiatric disorders were included in this study. All participants completed the Depression Anxiety Stress Scale 21 (DASS-21). The depression symptom score was calculated and interpreted as follows: less than 9: no depression; between 10 and 13: mild depression; between 14 and 20: moderate depression; between 21 and 27: severe depression, and more than 28: extremely severe depression. Results: The total number of participants in this study was 199. There was no correlation between age, thyroid stimulating hormone, and the DASS score. There was also no significant difference in the DASS-21 score between genders. However, there was a positive correlation between depression symptoms and stressful life events (r = 0.201, n = 199, p < 0.05). Conclusions: These findings would suggest that increased depression symptom scores correlate with increased stressful life events. A larger study should be undertaken to confirm these findings.